2019
DOI: 10.3390/cancers11122023
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Subtype of Hepatocellular Carcinoma with Poor Prognosis Based on Expression of Genes within the Glucose Metabolic Pathway

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent primary cancer and a highly aggressive liver malignancy. Liver cancer cells reprogram their metabolism to meet their needs for rapid proliferation and tumor growth. In the present study, we investigated the alterations in the expression of the genes involved in glucose metabolic pathways as well as their association with the clinical stage and survival of HCC patients. We found that the expressions of around 30% of genes involved in the glucose metabolic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 62 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…This study provided novel insights into the relationship between glycolysis and HCC. Another study 17 identified consistently dysregulated genes within the glucose metabolic pathways. On investigating the prognostic power of these genes on survival outcomes in HCC patients, two distinct molecular HCC subtypes were identified, with one subtype having significantly worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…This study provided novel insights into the relationship between glycolysis and HCC. Another study 17 identified consistently dysregulated genes within the glucose metabolic pathways. On investigating the prognostic power of these genes on survival outcomes in HCC patients, two distinct molecular HCC subtypes were identified, with one subtype having significantly worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The associations between HCC poor prognosis and down‐regulation in multiple metabolism enzymes have also been recognized in previous studies. [ 13 , 43 , 44 ] However, the reason remains unclear. Here, we found that the down‐regulation of metabolism pathways was largely caused by DNA hyper‐methylation in various metabolic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Its morbidity and mortality continue to rise, causing more than 600,000 deaths annually [1,2]. The symptoms and signs of early HCC are hard to notice, making its diagnosis often delayed, which is partly related to the poor prognosis [3][4][5]. In addition, due to host variabilities, individuals with the same pathological stage may still have significant differences in the overall survival (OS) [6].…”
Section: Introductionmentioning
confidence: 99%